Analisis Downtime Engine Motor Grader XCMG GR3005T Pro Menggunakan Metode Reliability Centered Maintenance II (RCM II) Dan Failure Mode And Effect Analysis (FMEA) - Arkan, Muhammad Arkan Adelard; Nyayu Aisyah; Lilik Dwi Setyana; Andhi Akhmad Ismail (Department of Mechanical Engineering, Vocational College, Gadjah Mada University., 2026)
The evaluation of engine system downtime in the XCMG GR3005T Pro motor grader was conducted using the Reliability-Centered Maintenance II (RCM II) and Failure Mode and Effects Analysis (FMEA) methods. Failure data and maintenance history from February 2023 to November 2024 were utilized to identify failure modes, calculate Risk Priority Number (RPN) values, and formulate appropriate maintenance actions. A total of 63 failure modes were identified across 23 engine components, with the Solenoid Fuel Supply Pump exhibiting the highest RPN value (126). Four major components were classified as critical components, namely the Solenoid Fuel Supply Pump, Oil Pump, Fuel Supply Pump, and Water Pump. The recommended maintenance strategies include Scheduled On-Condition Tasks and Scheduled Discard Tasks, determined based on the RCM II Decision Diagram evaluation. This approach is intended to reduce downtime, enhance engine system reliability performance, and maximize equipment availability.